Occurrence of enrofloxacin in overflows from animal lot and residential sewage lagoons and a receiving-stream. Issue 10 (October 2017) - Ikem, Abua; Lin, Chung-Ho; Broz, Bob; Kerley, Monty; Thi, Ho Le
Abstract: Enrofloxacin (ENRO), a fluoroquinolone, was quantified in overflows from an animal lot and residential sewage lagoons and in a receiving-stream (Gans Creek). The concentrations of ENRO in samples was determined by high-performance liquid chromatography − tandem mass spectrometry. In total, ninety samples including duplicates were analyzed during several monthly sampling campaigns. The samples collected represented the residential sewage lagoon overflow (RLO), animal lot lagoon overflow (ALLO), the combined overflows (RLO and ALLO), and Gans Creek (upstream, midstream and downstream positions). The frequency of detection of ENRO was 90% for RLO and 100% for both ALLO and Gans Creek. The highest concentration of ENRO (0.44 μg/L) was found in ALLO sample collected during high precipitation. ENRO levels found in RLO samples ranged from < LOQ to 259 ng/L and the highest value observed also coincided with high flow. The levels of ENRO found in Gans Creek ranged from 17–216 ng/L. A preliminary ecotoxicological assessment was conducted through calculation of the risk quotients (RQs) for organisms based on the ratio of the measured environmental concentrations in this study to the predicted-no-effect-concentrations (acute and chronic effect) data. From the RQs, high risks were observed for Microcystis aeruginosa (cyanobacteria; RQ = 4.4); Anabaena flosaquae (cyanobacteria; RQ = 1.3); and Lemna minor (aquatic vascular plant; RQ = 2.0). The long-term effects of mixtures of PHCs on Gans Creek watershed are probable.